Economic progress, social disquiet: the modern paradox - Eckersley, Richard (2001)
Surveys of social attitudes are revealing a perhaps unprecedented paradox: a booming economy but persistent community disquiet. The puzzling coincidence is fuelling interest in what is perhaps the ultimate public policy question: is life getting better - or worse? The relationship between economic growth and human development is not as clear-cut as conventional wisdom and government policy assume. Public opinion surveys suggest that the driving dynamic in Australia and other Western societies in the early decades of the new century will be a growing tension between values and lifestyles. How this tension is resolved will fundamentally determine national and global futures. - Reproduced
Keywords: Human development; Economic growth